Enhancing ASEAN Students’ Cross-Cultural Adaptability in Higher Education: Exploring the Issues of Applying Bilingual Education in China Panorama Curriculum - Fan, Haijing; Chano, Jiraporn (Universitas Negeri Makassar, 2024)
This research explores the issues of applying bilingual education in China Panorama Curriculum, with purpose to enhance cross-cultural adaptability of ASEAN students in higher education. Employing questionnaires and interviews with a longitudinal analysis based on factors like age, gender, nationality, and time in China, to investigate the cross-cultural adaptability of ASEAN students in China, focusing on psychological and learning environment adaptation. The research uncovers challenges in adapting to the Chinese cultural landscape and proposes solutions. Cultural disparities between China and ASEAN nations are identified, with the bilingual education approach proving beneficial in fostering classroom participation and cultural exchange. However, psychological challenges persist, impacting mental well-being and academic performance. The research reveals the limited social life of ASEAN students in China, confined to campus interactions, suggesting improvements in English proficiency among teachers and encouraging active student participation in social activities. While bilingual education holds promise, the research emphasizes the need for comprehensive strategies, including teacher training and addressing socioeconomic disparities. The findings offer insights into cross-cultural adaptation complexities, highlighting the potential of bilingual education within the Panorama Curriculum. Caution is advised when generalizing beyond ASEAN students in Guangxi, China, considering potential variations in cultural, social, and educational contexts internationally.